Research on Construction and Restoration Technology of Modern Historical Buildings. Issue 1 (June 2020) - Lei, Luo; Yong fa, Wu
Abstract: As an ancient civilization, China still has a lot of historical remains, but many historical buildings have been damaged to a certain extent during long-term use, and the safety of the buildings is difficult to guarantee. In response to this problem, it is necessary for relevant cultural departments to do a good job in the construction and restoration of historical buildings, and to highlight the cultural connotation of these buildings.